Transition from self-supported to supported living: Older people's experiences - Hvalvik, Sigrun (CoAction Publishing, 2011)
To become dependent on professional support to accomplish the daily activities of life can be considered a turning point, involving a range of challenging changes in life. The purpose of the study was to describe the experiences of older home-dwelling individuals in transition from self-supported to supported living from a lifeworld perspective. Five women and five men were interviewed, and a descriptive phenomenological design was used. The findings showed that an attitude of acceptance was an essential characteristic for this group. An attitude of acceptance comprised: flexibility and tolerance, recognition and hopes, and valuation of self and situation. Finding themselves in a situation they had to submit to, they took an attitude of acceptance. An attitude of acceptance implied acknowledgement of the situation as well as positivity and desires to manage. This attitude may represent a significant potential for improvement. Awareness of this is crucial to support older individuals in a healthy way through the transition process. An attitude of acceptance, however, also implied an acceptance of discontinuity in their lives, renunciations, and denigration of own needs. But this aspect of the acceptance was trivialized by the participants and not equally obvious. Insight into this complexity is vital to avoid ignorance of older individuals’ vulnerability in the transition process.